QSAR analysis of some azole derivatives as potent aromatase inhibitors - Razeih Sabet; Soghra Khabnadideh; Samaneh Mohseni; Ayyub Mojaddami; Zahra Rezaei (Shiraz University of Medical Sciences, 2018)
A high proportion of breast tumors are hormone-dependent, implying that endogenous estrogens play a critical role in cancer cell proliferation. One of the most effective strategies for the treatment of breast cancer is reduction of estrogens level by inhibiting aromatase enzyme which is responsible for catalyzing the rate-limiting step in estrogen biosynthesis. A series of azole derivatives as potential aromatase inhibitors were subjected to two different drug design methodologies, QSAR and molecular docking simulation. MLR, FA-MLR, PCR and GA-PLS were employed to make connections between the structural parameters and aromatase inhibitory activity. GA-PLS represented superior results and a model with a high statistical quality (R2 = 0.86 and Q2 = 0.83) for predicting the inhibitory activity. The results can provide useful information for the development of more potent aromatase inhibitors.